Effect of elevated CO2 on carbon partitioning in young Quercus ilex L. during resprouting - Aranjuelo, Iker; Pintó-Marijuan, Marta; Avice, Jean Christophe; Fleck, Isabel (Rapid Communications in Mass Spectrometry, 2011)
Stored carbon (C) represents a very important C pool with residence times of years to decades in tree organic matter. With the objective of understanding C assimilation, partitioning and remobilization in 2-year-old Quercus ilex L., those trees were exposed for 7 months to different [CO2] (elevated: 700 µmol mol−1; and ambient: 350 µmol mol−1 CO2). The 13C-isotopic composition of the ambient CO2 (ca. −12.8‰) was modified (to ca. −19.2‰) under the elevated CO2 conditions in order to analyze C allocation and partitioning before aerial biomass excision, and during the following regrowth (resprouting). Although after 7 months of growth under elevated [CO2], Q. ilex plants increased dry matter production, the absence of significant differences in photosynthetic activity suggests that such an increase was lower than expected. Nitrogen availability was not involved in photosynthetic acclimation. The removal of aboveground organs did not enable the balance between C availability and C requirements to be achieved. The isotopic characterization revealed that before the cutting, C partitioning to the stem (main C sink) prevented leaf C accumulation. During regrowth the roots were the organ with more of the labelled C. Furthermore, developing leaves had more C sink strength than shoots during this period. After the cutting, the amount of C delivered from the root to the development of aboveground organs exceeded the requirements of leaves, with the consequent carbohydrate accumulation. These findings demonstrate that, despite having a new C sink, the responsiveness of those resprouts under elevated [CO2] conditions will be strongly conditioned by the plant's capacity to use the extra C present in leaves through its allocation to other organs (roots) and processes (respiration). Copyright © 2011 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd
Keywords: carbon allocation; Cutting; Elevated CO2; leaves; Photosynthetic activity (voyant); Regrowth; roots

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Mediterranean natural forest living at elevated carbon dioxide: soil biological properties and plant biomass growth - Moscatelli, M C; Fonck, M; De Angelis, P; Larbi, H; Macuz, A; Rambelli, A; Grego, S (Soil Use and Management, 2001)
Abstract. Biomass productivity and soil microbial responses to long-term CO2 enrichment have been investigated in a Mediterranean natural forest ecosystem. Several biochemical parameters have been measured on soil samples taken from six open top chambers (OTCs), enclosing clumps of natural Mediterranean woody vegetation including: Quercus ilex L., Phillyrea angustifolia L., Pistacia lentiscus L. and Myrtus communis L. The CO2 concentration of the air inside the OTCs was either ambient or ambient plus 350 μmol mol–1 (c. 710 ppm as mean daily value). Microbial C biomass, microbial respiration, dehydrogenase, β-glucosidase, acid phosphatase and protease activities, inorganic N and soluble P, were tested in order to evaluate soil microbial size and activity. Statistically correlated seasonal patterns have been identified in some biochemical parameters in response to climatic conditions, soil nutritional status and the physiology of the vegetative cover. In situ soil respiration and above- and below-ground productivity were also measured. Microbial responses to CO2 enrichment were observed only at the beginning of the study and a general progressive reduction of the CO2 effect was recorded as monitoring continued. These results are in agreement with data from literature regarding similar studies on natural complex communities.
Keywords: Carbon dioxide; Forests; Mediterranean Region; microbial activities; roots; Soil; Soil enzymes

Mediterranean natural forest living at elevated carbon dioxide: soil biological properties and plant biomass growth - Moscatelli, M. C.; Fonck, M.; De Angelis, P.; Larbi, H.; Macuz, A.; Rambelli, A.; Grego, S. (Soil Use and Management, 2001)
Abstract. Biomass productivity and soil microbial responses to long-term CO2 enrichment have been investigated in a Mediterranean natural forest ecosystem. Several biochemical parameters have been measured on soil samples taken from six open top chambers (OTCs), enclosing clumps of natural Mediterranean woody vegetation including: Quercus ilex L., Phillyrea angustifolia L., Pistacia lentiscus L. and Myrtus communis L. The CO2 concentration of the air inside the OTCs was either ambient or ambient plus 350 μmol mol–1 (c. 710 ppm as mean daily value). Microbial C biomass, microbial respiration, dehydrogenase, β-glucosidase, acid phosphatase and protease activities, inorganic N and soluble P, were tested in order to evaluate soil microbial size and activity. Statistically correlated seasonal patterns have been identified in some biochemical parameters in response to climatic conditions, soil nutritional status and the physiology of the vegetative cover. In situ soil respiration and above- and below-ground productivity were also measured. Microbial responses to CO2 enrichment were observed only at the beginning of the study and a general progressive reduction of the CO2 effect was recorded as monitoring continued. These results are in agreement with data from literature regarding similar studies on natural complex communities.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Carbon dioxide; Forests; Mediterranean Region; microbial activities; roots; Soil; Soil enzymes

Fitomasa subterránea en pastizales semiáridos de dehesa. Estudio comparativo de cuatro transecciones - Gomez Gutiérrez, J M; BARRERA MELLADO, I; FERNÁNDEZ SANTOS, B; Guti, M E Z; Mellado, Barrera; Santos, Ndez (Pastos, 1988)
A comparative study of the underground phytomass (roots) valúes obtained along four transverse sections of four water courses was made in some semiarid grasslands, that are representative of the Central- Western área of Spain (Provinces of Avila and Salamanca). In order to perform this study, the following item's were studied: a) the total phyto- mass valúes for each profile (30 cm depth, 9 cm diameter), b) the hori- zons or 5 cm horizontal transect, in each section, c) the samples in each profile. Very similar sequences were observed in all the transects, high- lighting the effect of relief on underground phytomass, wich is considered a synthesis and an expression of the edaphicclimatic and anthropozoogenic action that governs its development. Key
Keywords: fitomasa subterránea; Grasslands; pastizales; raíces; roots; vaguada; water course